2013
DOI: 10.1155/2013/317685
|View full text |Cite
|
Sign up to set email alerts
|

Confusional State in HaNDL Syndrome: Case Report and Literature Review

Abstract: The syndrome of transient headache and neurologic deficits with cerebrospinal fluid lymphocytosis (HaNDL syndrome) is a self-limited condition. Confusional states are uncommonly reported as a clinical manifestation of this syndrome. Here, I report a 76-year-old female who presented with headache, confusion, and agitation with a mild CSF lymphocytosis. Other workup to determine the cause of her altered mental status was otherwise negative. The literature available in the English language on HaNDL syndrome is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…Although diverse clinical presentations of neurologic deficits are described, involuntary movements have not been reported. Gómez-Aranda presented 50 cases and reported that the most common neurologic deficit was sensory symptom (78% of episodes), followed by aphasia (66%), motor symptom (56%) and visual symptom (12%).2 The uncommon presentations such as confusional state, amnesia and cranial neuropathy have also been described 35. The transient neurologic deficits could occur before or during the headache.2 For our patient, the chorea occurred during the headache, while sensory and weakness occurred before the headache.…”
Section: Discussionmentioning
confidence: 99%
“…Although diverse clinical presentations of neurologic deficits are described, involuntary movements have not been reported. Gómez-Aranda presented 50 cases and reported that the most common neurologic deficit was sensory symptom (78% of episodes), followed by aphasia (66%), motor symptom (56%) and visual symptom (12%).2 The uncommon presentations such as confusional state, amnesia and cranial neuropathy have also been described 35. The transient neurologic deficits could occur before or during the headache.2 For our patient, the chorea occurred during the headache, while sensory and weakness occurred before the headache.…”
Section: Discussionmentioning
confidence: 99%
“…Etiology of HaNDL is not yet fully understood. Most studies suggest infectious, vascular and autoimmune mechanisms [5,6]. Currently, the main hypothesis is that this process is secondary to an activation of the immune system due to an infectious/inflammatory process, which activates the trigeminovascular system, leading to the development of focal neurological symptoms by a mechanism similar to the neuronal spreading depression seen in migraines with aura [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…65 HaNDL syndrome is a benign and self-limited disorder whose presentation can be protean, ranging from focal weakness 68 to altered mental status, and is classified as ICHD 7.3.5. 69 The SMART syndrome is an idiopathic disorder that is often found in patients treated with focal brain radiation for brain tumors and who develop transient headaches and focal neurological deficits about 2À10 years after radiation therapy. 67 …”
Section: The Diagnostic Challengementioning
confidence: 99%